Isobaric (vapour + liquid) equilibria of binary Pb-Sn and Sb-Sn system AT2Pa - Gao J.; Xu J.; Yang B.; Kong L.; Xu B.; You Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A new experimental method for determining vapor-liquid equilibrium (VLE) of binary alloys was designed in this study. The VLE data of Pb-Sn and Sb-Sn alloys were determined by using this new method. The experimental data passed the thermodynamic consistency test (Van Ness test), and the y(MAD) was 0.4066 and 0.6667, respectively, indicating that the experimental method is correct and reliable. The activity coefficient of Pb-Sn and Sb-Sn alloys was calculated by using the molecular interaction volume model (MIVM). The maximum average relative deviation Si and maximum average standard deviation Si* are ±1.34% and ±0.009, respectively, which indicates that the calculation of the activity coefficient of the Pb- Sn and Sb-Sn alloys by MIVM is reliable. The VLE data of Pb-Sn and Sb-Sn alloys were calculated based on the VLE theory and MIVM, and the calculated results agreed well with the experimental VLE data. The VLE phase diagrams of Pb-Sn and Sb-Sn alloys were also established in this study. The VLE phase diagrams offer a valid and intuitive way to analyze the product compositions’ dependence of temperature and pressure during the process of vacuum distillation. This will have immense significance in guiding the actual production of vacuum metallurgy.